THE IMPACT OF CULTURAL CONTEXT ON ENGLISH LANGUAGE TEACHING AND LEARNING - Musurmonova Chamangul Qobil qizi; Axatova Zebo (Recent scientific discoveries and methodological research, 2025)
Cultural context is a vital dimension of English language teaching (ELT) and learning that influences the teaching process, the learners, and language learning itself. Cultural values and social norms will impact learners in their approach to learning a language, influence teachers in curriculum design, and contribute to the learners' perceptions of the English language itself.